2022
DOI: 10.1002/hsr2.842
|View full text |Cite
|
Sign up to set email alerts
|

Color vision devices for color vision deficiency patients: A systematic review and meta‐analysis

Abstract: Background and Aims: There is insufficient evidence to support that using electronic or optical color vision devices improve color perception with current advanced technology. The purpose of this study is to compare and analyze the different color vision devices available for patients with color vision deficiency (CVD) and evaluate whether these devices improved their color perception.Methods: This review included randomized, experimental, comparative studies, as well as narrative reviews, prototype and innova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
1
6
1
Order By: Relevance
“…However, according to the Male et al (2023b) latest systematic reviews, in India, the overall prevalence has increased. The age group affected by the increased prevalence was children and adults.…”
Section: Prevalence and Impact Of Cvdmentioning
confidence: 99%
See 2 more Smart Citations
“…However, according to the Male et al (2023b) latest systematic reviews, in India, the overall prevalence has increased. The age group affected by the increased prevalence was children and adults.…”
Section: Prevalence and Impact Of Cvdmentioning
confidence: 99%
“…Moreover, only a few studies have documented the real global prevalence of CVD. Male et al (2023b) compiled the available literature and represented the prevalence of CVD globally by conducting a systematic review and meta-analysis, as shown in Table 2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Color vision deficiency (CVD) is an incurable congenital eye disorder that limits patient’s abilities to distinguish specific colors. Patients with CVD often need to use color vision filters like chromogen filters, tinted glass/lens to enhance their color perception, which is considered unesthetic (Badawy et al., 2018 ; Sekar et al., 2019 ; Male et al., 2022 ). Recently, with the development of metasurfaces and nanoparticle technology, innovative contact lenses for CVD have emerged.…”
Section: Novel Contact Lenses In Ophthalmic Diseasesmentioning
confidence: 99%
“…For more accurate color reproduction, it is necessary to shift from the CMF model of the standard colorimetric observer to CMFs that will take into account the individual characteristics of each person's vision. There are many studies on how to account for human visual perception in the imaging pipeline [1,2]. The important step in the direction connected with the display part of the pipeline was done in the research [3,4], where the principle of categorical observers has been proposed.…”
Section: Introductionmentioning
confidence: 99%